Jigsaw Type Cooperative Learning Model Using "Mabar Di Cape" Board Media Increases Interest and Mathematics Learning Outcomes - Ervitaviyan Wahyu Putri Pangestu; Yuli Witanto (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Students have difficulty in learning mathematics, which has an impact on low student learning outcomes. The purpose of this study was to analyze the effectiveness of the jigsaw cooperative learning model assisted by the MABAR DI CAPE board media on the interests and learning outcomes of mathematics in grade III Elementary School students. The type of research used was quasi-experimental research (quasi-experimental design) in the form of a nonequivalent control group design. The population in this study was 56 grade III students. The sampling technique used in this study used saturated samples. Data collection techniques used by researchers include unstructured interviews, observations, documentation, and tests. The research instruments used in this study were interview guidelines, observation guidelines, documentation guidelines, learning interest questionnaire sheets, and test questions. The research analysis technique used descriptive and statistical analysis. The results of the study showed that there was a difference in learning interest between students who used the jigsaw cooperative learning model and students who used the problem-based learning model in learning mathematics in grade III on the material of Multiplication of integers up to 100. The results of the hypothesis test also showed that students' learning interest in the experimental class was better than the learning interest in the control class. In addition, there is a significant difference in the learning outcomes of students between those who use the jigsaw-type cooperative learning model and those who use assistance in learning mathematics for grade III on the material of Multiplication of whole numbers up to 100. It is concluded that the jigsaw-type cooperative learning model applied in the experimental class is effective for the learning outcomes of grade III students on the material of Multiplication of whole numbers up to 100.